GROWTH AND YIELD RESPONSE OF GREEN SPINACH (AMARANTHUS SPP.) TO THE APPLICATION OF CHICKEN MANURE AND COW BLOOD KASGOT ORGANIC FERTILIZER - Syafira, Ayu
Green spinach (Amaranthus spp.) is a vegetable plant that contains quite a lot of iron. In 2022, spinach productivity will decrease by 2.89% with total productivity only reaching 1,129.67 quintals/ha. Therefore, green spinach productivity needs to be increased. One effort to increase the productivity of green spinach in a sustainable manner is through the provision of used kasgot organic fertilizer. This research aims to determine the response of growth and yield of green spinach to the application of kasgot organic fertilizer derived from chicken manure and cow blood as a substrate. The research design used was a Completely Randomized Design with one treatment factor, which is the dose of kasgot organic fertilizer consisting of five treatment levels of kasgot doses, (0, 5, 10, 15, and 20 tonnes/ha) with five replications. Treatment with a dose of 15 tonnes/ha of kasgot organic fertilizer increased the growth and yield of green spinach significantly. The administration of various doses of kasgot organic fertilizer showed a quadratic response pattern for all parameters which was characterized by a decrease in growth and yield at the highest dose so that fertilizer dose optimization could be carried out. The optimum dose of kasgot organic fertilizer recommended to increase the growth and yield of green spinach is 13.94 tonnes/ha